“Em meus pensamentos você está tão longe”: manifestações da morte na arte contemporânea - Gabriel de Souza Santana (2023)
This research searches among the works of contemporary artists for manifestations of death that emerge from the long artistic tradition with the theme in its broad scope. It starts from a historical panorama that, using a Warburg perspective, suggests the survival (Nachleben) of images linked to death in the collective imaginary and the emergence of new codes based on the old ones that refuse their death into oblivion. In today's world-moment that is so scientific and materialistic, yet deeply aesthetic and symbolic, death is interdicted, but it constantly breaks its block through mass culture and the fine arts. In this flow of survivals, current images are divided in this research into four domains, namely: the violence of power, the memories of time, the apocalypse of nature and the survival of the spirit. In these domains reside the imagery symbols of contemporary death and survivals from remote eras that were believed to have been long gone. It concludes that artists have reflected on collective and individual finitude in different ways to reestablish the links between death and life in addition to playing with the undead state of cosmopolitan society.